The Effect of Competence and Training on the Effectiveness of Teacher Training Vocational School at Serang Region, Banten - Sri Mulyati (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
This study aims to determine competence and training on Vocational School Teacher Training Effectiveness in the Serang Region, Banten. The method used is explanatory research with analytical techniques using statistical analysis with regression, correlation, determination, and hypothesis testing. This study shows that competence has a significant effect on the effectiveness of teacher training by 47.8%, hypothesis testing is obtained t count > t table or (7,472 > 2,000). Training has a significant effect on the effectiveness of teacher training by 44.6%; hypothesis testing is obtained t count > t table or (7,002 > 2,000). Competence and training simultaneously have a significant effect on the effectiveness of teacher training with the regression equation Y = 8.314 + 0.429X1 + 0.368X2, and the contribution of the effect is 58.0%.